Material properties of zinc phthalocyanine from Fa solution and application in organic solar cells [Articol] - Potlog, Tamara; Furtuna, Vadim; Rusnac, Roman; Rotaru, Cornel; Masuzawa, Tomoaki; Mimura, Hidenori; Robu, Stefan (IJIEEE, 2018)
This paper presents for a first time asolution-processableZnPc thin films from formic acid (FA) solution by drop casting method and the photovoltaic parameters of the Organic Solar Cells (OPV) based on ZnPc-diode Schottky.Structural and optical propertiesof ZnPc thin films were investigated by X-raydiffraction (XRD),Fourier transform infrared spectroscopy (FTIR) and UV-VIS spectroscopy.XRD analysis show phase transformation of the alpha-beta phases of ZnPc thin films to beta phase due to the annealing in H 2 atmosphere at 400 o C for 30 min. FTIR analysis show that the formate ion (HCOO −) is attached to Zn(II)Pc. Further on, ITO/PEDOT: PSS/ZnPc(I 2)/Al Schottkyphotovoltaic devices with efficiency of 0.3 % were prepared and their characteristics 'enhancement is discussed. The values for the opencircuit voltage (1.03 V) and the current density (8.2 µA/cm 2) are higher than in the case of Schottky diode devices obtained by thermal vacuum evaporation.
Keywords: Drop Casting Method; Zinc Phthalocyanine; Formic Acid; Thin Film; Organic Solar Cells